Ketogenic Diet for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The efficacy of the ketogenic diet in 58 children with multiple seizure types resistant to antiepileptic drugs has been evaluated at the Johns Hopkins University School of Medicine, Baltimore.